Influência da faixa etária e sexo nos parâmetros hematológicos e bioquímicos séricos de bezerros da raça Senepol do nascimento a desmama - Gomes, Lara Reis (2016)
Chapter 2 - The objective of this study was to evaluate haematological parameters sequentially in Senepol breed calves from birth to weaning, verify the influence of sex and compare the results among age groups. 42 calves of the Senepol breed were used (18 females and 24 males), chosen at random, all of which came from artificial insemination and embryo transfer. The animals were accompanied since the first week of life up to 240 days old. Ten (10) blood samples were obtained from every animal during the following periods: from 1 to 7, 15, 30, 60, 90, 120, 150, 180, 210 and 240 days of age (weaning). Three ml of blood were collected in sterile tubes containing anticoagulant EDTA K3 (tripotassium etilenodiaminotetracetico acid), from the external jugular venipuncture for the complete hemogram. The samples were processed in the veterinary Hematology Sysmex PocH 100 iv diff TM analyzer and blood extensions were made for the blood differential leukocyte count. For statistical analysis we used the Kruskal-Wallis test (p < 0.05) to test the difference between the age groups and the Mann-Whitney test (p < 0.05) to assess the difference between the sexes in different periods. There was statistical difference (p < 0.05) in all parameters of the hemogram, except for the count of basophils and monocytes (p > 0.05). Influence of sex was not observed (p < 0.05) in the hematological parameters studied. We concluded there is influence of age in hematological parameters of the Senepol breed calves from birth to weaning, however we did not observe any influence of sex in the hematological parameters. Chapter 3 - The objective of this study was to evaluate the influence of sex and age factors in serum biochemical parameters of the Senepol breed calves from birth to weaning. 42 calves of the Senepol breed were used (18 females and 24 males), coming from artificial insemination and embryo transfer. The animals were accompanied from the first week of life up to 240 days old. Ten (10) blood samples were obtained from every animal during the following periods: from 1 to 7, 15, 30, 60, 90, 120, 150, 180, 210 and 240 days of age (weaning). We collected four ml of blood from each animal in each period from the external jugular venipuncture in sterile tubes with separator gel and clot activator to obtain the serum. The samples were processed in automatic multichannel Analyzer ChemWell, previously calibrated with Calibra H and benchmarked with universal control serum qualitrol H. For statistical analysis we used the Kruskal-Wallis test (p < 0.05), to test the difference between the age groups, and the Mann-Whitney test (p < 0.05) to assess the difference between the sexes in the different periods. We verified the influence of age on serum biochemical parameters evaluated (p < 0.05). Regarding the comparison between males and females, there was statistical difference (p < 0.05) only for CK. We concluded that there is influence of age and gender on the values of serum biochemical parameters of the Senepol breed calves from birth to weaning. Chapter 3: The objective of this study was to evaluate the influence of sex and age factors in serum biochemical parameters of the Senepol breed calves from birth to weaning. 42 calves of the Senepol breed were used (18 females and 24 males), coming from artificial insemination and embryo transfer. The animals were accompanied from the first week of life up to 240 days old. Ten (10) blood samples were obtained from every animal during the following periods: from 1 to 7, 15, 30, 60, 90, 120, 150, 180, 210 and 240 days of age (weaning). We collected four ml of blood from each animal in each period from the external jugular venipuncture in sterile tubes with separator gel and clot activator to obtain the serum. The samples were processed in automatic multichannel Analyzer ChemWell, previously calibrated with Calibra H and benchmarked with universal control serum qualitrol H. For statistical analysis we used the Kruskal-Wallis test (p < 0.05), to test the difference between the age groups, and the Mann -Whitney test (p < 0.05) to assess the difference between the sexes in the different periods. We verified the influence of age on serum biochemical parameters evaluated (p < 0.05). Regarding the comparison between males and females, there was statistical difference (p < 0.05) only for CK. We concluded that there is influence of age and gender on the values of serum biochemical parameters of the Senepol breed calves from birth to weaning